2008
DOI: 10.1007/s10661-008-0361-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genotoxicity of coal fly ash in Allium cepa root cells by combining comet assay with the Allium test

Abstract: Fly ash is a by-product of coal-fired electricity generation plants. Its utilization and disposal is of utmost importance. Using onion (Allium cepa) root tip system, the present study was carried out to evaluate the potential toxic and genotoxic effects of fly ash, collected from a thermal power plant in West Bengal, India. Prior to testing, the collected fly ash sample was mixed with sand in different proportions. Allium bulbs were allowed to germinate directly in fly ash and after five days the germinating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…Phragmoplast is a plant cell specific structure forms during cytokinesis and serves as a scaffold for cell plate assembly and subsequent formation of a new cell wall separating two daughter cells. It is a complex assembly of microtubules, microfilament and endoplasmic reticulum [27]. Multinucleate cells were common in all the concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Phragmoplast is a plant cell specific structure forms during cytokinesis and serves as a scaffold for cell plate assembly and subsequent formation of a new cell wall separating two daughter cells. It is a complex assembly of microtubules, microfilament and endoplasmic reticulum [27]. Multinucleate cells were common in all the concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The application of Comet assay is considered to be a rapid, sensitive, inexpensive and simple method for detecting DNA damage on root meristem of individual cells of A. cepa (Chakraborty et al 2009, Phugare et al 2011a). The results of Comet assay demonstrated that the root meristem of A. cepa bulbs showed genetic damage in the presence of textile effl uent as the chromosomal material integrity was disturbed as well as it was oozing out in the form of bulging in nuclear membrane showing comet like structure (Fig.…”
Section: Detoxifi Cation Studiesmentioning
confidence: 99%
“…The DNA damage studies were carried out using Comet assay, that is, single cell gel electrophoresis (SCGE) according to Singh [17] with slight modification [10,18]. Roots from the same bulbs as has been used for Allium test and anaphase-telophase chromosome aberration assay were used for comet assay following 48 h treatment.…”
Section: Comet Assaymentioning
confidence: 99%
“…The Allium test is a well known and convenient method used in laboratories owing to the ease of their storage and germination, and more over can be used as a convenient system for the evaluation of macroscopic (measure of EC 50 ) and microscopic (micronuclei formation, chromosome aberrations) parameters pertaining to genotoxicity [9]. Apart from Allium test, Allium cepa has been used successfully in our laboratory as a biomarker of genotoxicity using comet assay [10]. Comet assay is a simple, sensitive and effective technique used to quantitatively express the extent of genotoxicity of many hazardous agents and has been used widely in genotoxicity monitoring of the environment.…”
Section: Introductionmentioning
confidence: 99%